(untitled) (Tanzania Medical Journal, 2022)
Introduction Ventriculoperitoneal (VP) shunting is used to manage hydrocephalus, and many complications have been reported with this intervention. Abdominal pseudocysts are relatively rare but do occur as a complication in patients with VP shunts. Case report We report of a case of a seven-year-old boy with congenital hydrocephalus and VP shunt in situ who presented with a two-week history of headaches and abdominal pain accompanied by partial constipation. Abdominal CT-scan revealed an intra-abdominal pseudocyst. The boy was operated, recovered well and was discharged with no complications. Conclusion Due to its low incidence and unspecific symptomatology, it is easy to overlook an intraperitoneal pseudocyst. As relatively cheap and non-invasive diagnostic modalities are available, it is worth to do an ultrasound in patients presenting with failure of VP shunts as well as abdominal complaints.